Peculiarities of inflammatory response during collagenosis - N. A. Trofimenko; V. N. Zorina; S. V. Arkhipova; Ya. A. Gorbatovsky; R. M. Zorina (Бюллетень сибирской медицины)
Concentrations of cytokines (IL-1β, IL-6, TNF-α) of α2-macroglobulin (MG), α1-antitrypsin (AT) plasminogen (PL), whole protein, albumin and uric acid in blood serum of patients with collagenosis have been investigated aiming the study of their complex interaction and the possibility of their use during differential diagnostics. The blood serum of 60 healthy donors, 53 patients with rheumatoid arthritis (RA), 15 patients with reactive arthritis (REA) and 16 patients with systemic lupus erythematosus (SLE) has been studied. IL-1β, IL-6 and TNF-α concentrations have been defined by ELISA, MG, AT and PL-rocket immunoelectrophoresis, the whole protein, albumin and uric acid — by biochemical methods. The albumin level decreased in all groups of patients. The whole protein concentration decreased at the first RA activity degree. MG, AT and PL levels had no difference at all diseases as compared to the control group. IL-6 concentration increased significantly at all patients groups. TNF-α increased with the RA severity but differed statistically significantly from REA and SLE only at the most severe degree. Analogous trends in IL-1β concentration have been found in cases of RA and SLE but at REA great individual fluctuations with the high average level have been found. Synchronous change of the studied cytokine concentrations without associated MG level change is evidence of the damage of traffic and regulatory functions of this protein. The uric acid can be used for SLE diagnostics and the dynamic supervision of IL-1β and TNF-α can be a prognostic criterion at RA.